Measurable Residual Disease and Fusion Partner Independently Predict Survival and Relapse Risk in Childhood KMT2A-Rearranged Acute Myeloid Leukemia: A Study by the International Berlin-Frankfurt-Münster Study Group - van Weelderen, Romy E; Klein, Kim; Harrison, Christine J; Jiang, Yilin; Abrahamsson, Jonas; Arad-Cohen, Nira; Bart-Delabesse, Emmanuelle; Buldini, Barbara; De Moerloose, Barbara; Dworzak, Michael N; Elitzur, Sarah; Fernández Navarro, José M; et al. (Journal of clinical oncology, 2023)
PURPOSE: A previous study by the International Berlin-Frankfurt-Münster Study Group (I-BFM-SG) on childhood KMT2A-rearranged (KMT2A-r) AML demonstrated the prognostic value of the fusion partner. This I-BFM-SG study investigated the value of flow cytometry-based measurable residual disease (flow-MRD) and evaluated the benefit of allogeneic stem-cell transplantation (allo-SCT) in first complete remission (CR1) in this disease. METHODS: A total of 1,130 children with KMT2A-r AML, diagnosed between January 2005 and December 2016, were assigned to high-risk (n = 402; 35.6%) or non-high-risk (n = 728; 64.4%) fusion partner-based groups. Flow-MRD levels at both end of induction 1 (EOI1) and 2 (EOI2) were available for 456 patients and were considered negative (<0.1%) or positive (≥0.1%). End points were 5-year event-free survival (EFS), cumulative incidence of relapse (CIR), and overall survival (OS). RESULTS: The high-risk group had inferior EFS (30.3% high risk v 54.0% non-high risk; P < .0001), CIR (59.7% v 35.2%; P < .0001), and OS (49.2% v 70.5%; P < .0001). EOI2 MRD negativity was associated with superior EFS (n = 413; 47.6% MRD negativity v n = 43; 16.3% MRD positivity; P < .0001) and OS (n = 413; 66.0% v n = 43; 27.9%; P < .0001), and showed a trend toward lower CIR (n = 392; 46.1% v n = 26; 65.4%; P = .016). Similar results were obtained for patients with EOI2 MRD negativity within both risk groups, except that within the non-high-risk group, CIR was comparable with that of patients with EOI2 MRD positivity. Allo-SCT in CR1 only reduced CIR (hazard ratio, 0.5 [95% CI, 0.4 to 0.8]; P = .00096) within the high-risk group but did not improve OS. In multivariable analyses, EOI2 MRD positivity and high-risk group were independently associated with inferior EFS, CIR, and OS. CONCLUSION: EOI2 flow-MRD is an independent prognostic factor and should be included as risk stratification factor in childhood KMT2A-r AML. Treatment approaches other than allo-SCT in CR1 are needed to improve prognosis.
Keywords: homologní transplantace; Neoplasm, Residual; reziduální nádor; lidé; Leukemia, Myeloid, Acute; Transplantation, Homologous; Humans; Prognosis; Recurrence; Myeloproliferative Disorders; prognóza; Hematopoietic Stem Cell Transplantation; myeloproliferativní poruchy; dítě; transplantace hematopoetických kmenových buněk; Child; akutní myeloidní leukemie; recidiva